Assessment of Supply Chain Greenness: A Literature Review - (:unkn) unknown (IGI GLOBAL, 2018)
Having become conscious about the importance of the environment much more than past nowadays, the environmentally benign applications also called as green applications have increased tremendously in the recent years. Although there are specific and individual studies in various fields from design of product to final delivery of it, there is a need to handle the subject as a whole and construct green supply chains. Before constructing a green supply chain, the first step is to assess the existing structure from the viewpoint of greenness. Hence, it is important to develop a systematic assessment approach and this study aims to analyze the existing literature by mainly clarifying the criteria and methods used in such assessment systems and provide directions for future studies. Moreover, this study also aims to provide a base for the academics and practitioners that are willing to develop a greenness assessment methodology for supply chains. For this aim, numerous studies have been analyzed under a proposed structure including four sub-sections which consist of a green supply chain.
Keywords: PERFORMANCE EVALUATION; MANAGEMENT; PRESSURES